Autonomous Vehicle Radiation Based on Traffic Flow Analysis - Kordelia, Cut Dona; Armizoprades, Armizoprades (Educativo: Jurnal Pendidikan, 2022)
The transportation sector is heading to a new futuristic era, the fully-autonomous vehicles. Radar, lidar, and Sonar are considered critical aspects of self-driving technology. However, these sensors come with inherent danger. Their exposure has a hazardous impact on humans and living things. A forecast made using the level of service classification shows that there will be excessive radiation exposure when these cars dominate the traffic. This prediction must be taken into account when designing a level-five autonomous fleet.